Transcranial direct current stimulation impairs updating of avoidance-based associative learning - van ’t Wout-Frank, Mascha; Garnaat, Sarah L.; Faucher, Christiana R.; Arulpragasam, Amanda R.; Cole, Julia E.; Philip, Noah S.; Burwell, Rebecca D. (Frontiers in Human Neuroscience, 2023)
Exposure-based psychotherapies for the treatment of anxiety- and fear-based disorders rely on “corrective” associative learning. Namely the repeated confrontation with feared stimuli in the absence of negative outcomes allows the formation of new, corrected associations of safety, indicating that such stimuli no longer need to be avoided. Unfortunately, exposure-facilitated corrective learning tends to be bound by context and often poorly generalizes. One brain structure, the prefrontal cortex, is implicated in context-guided behavior and may be a relevant target for improving generalization of safety learning. Here, we tested whether inhibition of the left prefrontal cortex causally impaired updating of context-bound associations specifically or, alternatively, impaired updating of learned associations irrespective of contextual changes. Additionally, we tested whether prefrontal inhibition during corrective learning influenced subsequent generalization of associations to a novel context. In two separate experiments, participants received either 10 minutes of 2mA cathodal transcranial direct current stimulation (tDCS) over EEG coordinate F3 (Experiment 1 n=9, Experiment 2 n=22) or sham stimulation (Experiment 1 n=10, Experiment 2 n=22) while previously learned associations were reversed in the same or a different context from initial learning. Next, to assess generalization of learning, participants were asked to indicate which of the previously seen images they preferred in a novel, never seen before context. Results indicate that tDCS significantly impaired reversal irrespective of context in Experiment 2 only. When taking learning rate across trials into account, both experiments suggest that participants who received sham had the greatest learning rate when reversal occurred in a different context, as expected, whereas participants who received active tDCS in this condition had the lowest learning rate. However, active tDCS was associated with preferring the originally disadvantageous, but then neural stimulus after stimulus after reversal occurred in a different context in Experiment 1 only. These results support a causal role for the left prefrontal cortex in the updating of avoidance-based associations and encourage further inquiry investigating the use of non-invasive brain stimulation on flexible updating of learned associations.